2000
DOI: 10.1080/01411920050030914
|View full text |Cite
|
Sign up to set email alerts
|

Student Attitudes, Image and the Gender Gap

Abstract: This article, based on a 3 year study in East Anglian schools, draws on a range of evidence pointing to different attitudes of girls and boys to General Certi cate of Secondary Education (GCSE) work. Suggestions are made to account for these differences, with particular emphasis being placed on peer pressure, image and social groupings. Although these are relevant to both sexes, it was found to be more acceptable for girls to work hard and still be part of the 'in crowd', whilst boys were under greater pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
2
15

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 22 publications
12
121
2
15
Order By: Relevance
“…However, there have been studies on gender differences in the many components of student engagement (e.g., intrinsic motivation and persistence in school work) (Barber, 1996;Darom & Rich, 1988;Warrington, Younger, & Williams, 2000). As intrinsic motivation and persistence constitute the first two dimensions of student engagement, these findings will have implications regarding gender differences in student engagement.…”
Section: Gender Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been studies on gender differences in the many components of student engagement (e.g., intrinsic motivation and persistence in school work) (Barber, 1996;Darom & Rich, 1988;Warrington, Younger, & Williams, 2000). As intrinsic motivation and persistence constitute the first two dimensions of student engagement, these findings will have implications regarding gender differences in student engagement.…”
Section: Gender Considerationsmentioning
confidence: 99%
“…As intrinsic motivation and persistence constitute the first two dimensions of student engagement, these findings will have implications regarding gender differences in student engagement. It has been reported that boys are less motivated than girls and spend less time doing homework and that boys have lower expectations of themselves and are less enthusiastic about continuing their studies (Barber, 1996;Cox, 2000;Darom & Rich, 1988;Hatzichristou & Hopf, 1996;Warrington et al, 2000). As for the cognitive dimension of student engagement, there is also evidence showing that girls are more likely than boys to plan, monitor, and regulate their cognitions and study activities (Ablard & Lipschultz, 1998;KenneyBenson, Pomerantz, Ryan, & Patrick, 2006;Patrick, Ryan, & Pintrich, 1999;Zimmerman & Martinez-Pons, 1990).…”
Section: Gender Considerationsmentioning
confidence: 99%
“…Female students had a higher GPA than male students. Several reasons for this gender gap in achievement are suggested, including home and school/classroom environment, socio-economic factors, peer culture, gender differences in attitudes towards school work (Warrington, Younger, & Williams, 2000), and degree of selfdiscipline (Duckworth & Seligman, 2006). Consequences are a higher degree of special education and higher dropout rates among men (Legewie & DiPrete, 2012), which lead to a range of possible negative concerns related to work status, income, behaviour, and quality of life (Belfield & Levin, 2007).…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Involvement in heavy drinking and other entertainment activities, poor class attendance, negative attitude towards studies, lack of practice, waiting until too late to study, studying only for passing examinations instead of understanding, and failure to seek assistance from lecturers and colleagues were mentioned as factors that hamper male students' performance. According to respondents of this study it appears the "macho" behaviour described by Warrington, Younger, and Williams (2000) could be associated with male accounting students at the University of Botswana. Male students' lack of seriousness towards their studies was summarized by one female student in the following words: What emerged from 176 responses which were given to this question was that academic performance is the function of an individual's commitment and determination to succeed.…”
Section: Analysis Of Qualitative Questionsmentioning
confidence: 76%
“…Harding (1986) asserted that feminism itself was responsible for bringing about radical changes in the ways girls perceived themselves, where they could no longer perceive their identify in mainly domestic terms but rather as much as workers as homemakers. Warrington, Younger and Williams (2000) revealed that because of "macho" male culture boys were more likely than girls to be ridiculed by their peers for working hard at school, and frequently resorted to "laddish" behaviour such as challenging authority, drawing attention to themselves and pretending not to care about school work in order to gain acceptance from their peer group. Gallagher (2001) holds the view that boys and girls display different academic performance not because they differ in their physical, emotional and intellectual development but rather due to some social and cultural factors.…”
Section: Out Of School Factors (Social Culture)mentioning
confidence: 99%